2016
DOI: 10.1136/archdischild-2015-310122
|View full text |Cite
|
Sign up to set email alerts
|

Season and region of birth as risk factors for coeliac disease a key to the aetiology?

Abstract: BackgroundCoeliac disease (CD) incidence has increased in recent decades, characterised by variations according to sex, age at diagnosis, year of birth, month of birth and region of birth. Genetic susceptibility and exposure to gluten are the necessary factors in CD aetiology, although several environmental factors are considered.MethodsA nationwide prospective cohort longitudinal study was conducted consisting of 1 912 204 children aged 0–14.9 years born in Sweden from 1991 to 2009. A total of 6569 children w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 39 publications
1
19
0
Order By: Relevance
“…This may adversely influence the development of the fetus' immune system with consequences later in life [36]. In agreement, earlier studies have reported a lower risk of developing CD for winter-born compared to summer-born children [12][13][14][15][16]37,38].…”
Section: Season Of Birth and Risk Of Developing CDsupporting
confidence: 71%
See 2 more Smart Citations
“…This may adversely influence the development of the fetus' immune system with consequences later in life [36]. In agreement, earlier studies have reported a lower risk of developing CD for winter-born compared to summer-born children [12][13][14][15][16]37,38].…”
Section: Season Of Birth and Risk Of Developing CDsupporting
confidence: 71%
“…Indeed, children born in summer/autumn often begin weaning and have their first exposure to gluten during the winter period, which is characterized by higher exposure to seasonal viruses. Viral infections influence flora and permeability of the intestine, and other studies have suggested that this may play a role in the etiology of CD [16,39]. Indeed, a recent study reported that reovirus infection may trigger CD in some patients [40].…”
Section: Season Of Birth and Risk Of Developing CDmentioning
confidence: 98%
See 1 more Smart Citation
“…We found that 699 of 308 903 live births in one Israeli hospital were diagnosed with CD and autumn births were associated with a higher risk for developing CD, with an incidence ratio of 1.22. The autumn high season increased the incidence ratio even higher to 1.40. autumn increased the risk for future CD compared with birth during the winter (19). A study conducted in central Israel found that births during the autumn were associated with CD (20).…”
Section: Key Notesmentioning
confidence: 99%
“…In the USA, celiac disease has been found to be most prevalent in the Northeast and the Midwest regions [ 30 ], where the great majority of cases of B. burgdorferi infection also occur [ 19 ]. In Sweden, the highest incidence of celiac disease has been associated with the southern region [ 31 ], where Lyme disease is endemic [ 32 ]. Despite the similar pattern of geographic distribution and the publicized conjecture regarding a potential link between celiac disease and Lyme borreliosis, studies to assess such an association are lacking.…”
Section: Introductionmentioning
confidence: 99%